Napak Tilas Warisan Sufi Persia di Nusantara - Lukman Hakim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
No one denies that the Persians have a unique culture and a brilliant intellectualism that becomes the center of the glorious history of human civilization. Persian triumph has influenced widely not only through the entire Islamic region in the world but also to the archipelago. One of the most prominent Persian influences in the development of Islamic teaching in archipelago is mystical ideas which derived from the Persian Sufi tradition. One of a growing pattern sufism in Indonesia which is typical of Persian is the concept of Wahdat al-wujud, ittihat and hulul. These three concepts put forward about the unification of the Creator (Khaliq) to the creature (Makhluk) who allegedly have links with faith communities Zoroasterian believed by pre-Islamic Persian. Finally, the Islamic civilization which flourished in Indonesia is a the combination of Islamic teachings and the spirit of the Persian spiritualism. This synthesis has led to a unique form and model of Islam that also raises a dynamic and controversial Sufi thought in the archipelago (Indonesia)